The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1021/np50106a021
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase Inhibitors from Anacardium occidentale Fruits

Abstract: Anacardic acids, 2-methylcardols, and cardols isolated from various parts of the cashew [Anacardium occidentale] (Anacardiaceae) fruit have been found to exhibit tyrosinase inhibitory activity. Kinetic studies with the two principal active compounds, 6-[8(Z),11(Z),14-pentadecatrienyl]salicylic acid and 5-[8(Z),11(Z),14-pentadecatrienyl]resorcinol, have indicated that both of these phenolic compounds exhibit characteristic competitive inhibition of the oxidation of L-3,4-dihydroxyphenylalanine (L-DOPA) by mushr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(98 citation statements)
references
References 13 publications
5
83
0
10
Order By: Relevance
“…É originária do Brasil, e utilizada na medicina tradicional, principalmente no Nordeste brasileiro com efeitos terapêuticos como: aliviar dor de dente, antiinfl amatório para gengiva e garganta, bronquites, artrites, cólicas intestinais, icterícia, contra diabetes, asma e até mesmo usado como afrodisíaco (Mota, 2004;Olumayokun et al, 2004;Morais et al, 2005;Agra et al, 2007). Na literatura encontram-se atividades farmacológicas comprovadas, como sendo o cajueiro uma planta antiifl amatória (Olajide et al, 2004;Falcão et al, 2005), antidiabética Salto, 1987Salto, /1989Kamtchouing et al, 1998;Barbosa-Filho et al, 2005); inibidor da enzima acetilcolinesterase (Barbosa-Filho et al, 2006) e substâncias isoladas do fruto demonstraram ser inibidora de tirosinase (Kubo et al, 1994).…”
Section: Introductionunclassified
“…É originária do Brasil, e utilizada na medicina tradicional, principalmente no Nordeste brasileiro com efeitos terapêuticos como: aliviar dor de dente, antiinfl amatório para gengiva e garganta, bronquites, artrites, cólicas intestinais, icterícia, contra diabetes, asma e até mesmo usado como afrodisíaco (Mota, 2004;Olumayokun et al, 2004;Morais et al, 2005;Agra et al, 2007). Na literatura encontram-se atividades farmacológicas comprovadas, como sendo o cajueiro uma planta antiifl amatória (Olajide et al, 2004;Falcão et al, 2005), antidiabética Salto, 1987Salto, /1989Kamtchouing et al, 1998;Barbosa-Filho et al, 2005); inibidor da enzima acetilcolinesterase (Barbosa-Filho et al, 2006) e substâncias isoladas do fruto demonstraram ser inibidora de tirosinase (Kubo et al, 1994).…”
Section: Introductionunclassified
“…Previous studies have demonstrated that the crude extracts of A. occidentale had numerous biological applications Olajide et al, 2005;Ojewole, 2004;Franca et al, 1993;Kubo et al, 1994). Reports showed that the aqueous, alcoholic and hexane extracts from the barks and leaves of A. occidentale had hypoglycemic effects (Ojewole, 2003;Alexander-Lindo et al, 2004;Sokeng et al, 2001;Kamtchouing et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In plants surveyed, in addition to flavonoids, other phenols were found such as caffeic and chlorogenic acid in Achyrocline satureioides (Desmarchelier et al, 2000) and chlorogenic acid in Trichilia catigua (Lagos, 2006), besides anacardic acid in Anacardium ocidentale (Kubo et al, 1994). (Barron & Ibrahim, 1996) www.intechopen.com Studies conducted by Ko and colleagues (2004) in flavonoids as inhibitors of PDE have suggested that C-4' and C-5' hydroxyl groups is not important for PDE-5 inhibition.…”
Section: Flavonoids and Other Phenolic Compoundsmentioning
confidence: 99%